Hydroxychloroquine decreases human MSC‐derived osteoblast differentiation and mineralization in vitro. Issue 2 (3rd October 2017) - Both, Tim; van de Peppel, H. Jeroen; Zillikens, M. Carola; Koedam, Marijke; van Leeuwen, Johannes P. T. M.; van Hagen, P. Martin; van Daele, Paul L. A.; van der Eerden, Bram C. J.
Abstract: We recently showed that patients with primary Sjögren Syndrome (pSS) have significantly higher bone mineral density (BMD) compared to healthy controls. The majority of those patients (69%) was using hydroxychloroquine (HCQ), which may have favourable effects on BMD. To study the direct effects of HCQ on human MSC‐derived osteoblast activity. Osteoblasts were cultured from human mesenchymal stromal cells (hMSCs). Cultures were treated with different HCQ doses (control, 1 and 5 µg/ml). Alkaline phosphatase activity and calcium measurements were performed to evaluate osteoblast differentiation and activity, respectively. Detailed microarray analysis was performed in 5 µg/ml HCQ‐treated cells and controls followed by qPCR validation. Additional cultures were performed using the cholesterol synthesis inhibitor simvastatin (SIM) to evaluate a potential mechanism of action. We showed that HCQ inhibits both MSC‐derived osteoblast differentiation and mineralization in vitro . Microarray analysis and additional PCR validation revealed a highly significant up‐regulation of the cholesterol biosynthesis, lysosomal and extracellular matrix pathways in the 5 µg/ml HCQ‐treated cells compared to controls. Besides, we demonstrated that 1 µM SIM also decreases MSC‐derived osteoblast differentiation and mineralization compared to controls. It appears that the positive effect of HCQ on BMD cannot be explained by a stimulating effect on the MSC‐derived osteoblast. The discrepancy between high BMD and decreased MSC‐derived osteoblast function due to HCQ treatment might be caused by systemic factors that stimulate bone formation and/or local factors that reduce bone resorption, which is lacking in cell cultures.